Developing parasitic architecture as a tool for propagation within cities - Given, Daniel (Journal of Architecture and Urbanism, 2021)
The term ‘parasitic architecture’ is an overused, and misunderstood buzzword within the architectural and urban planning community. By breaking down, through case study, how a space is developed and evolves, reclassification of architectural parasites is possible. Focusing on how parasitic architecture has produced urban growth and development of community within Tokyo as the primary case study, the reclassification is based in pre-existing architectural development and the nature of actual, living parasites. This reclassification of architectural parasite produces three separate types of parasite; the ‘structured,’ ‘symbiotic’ and the ‘hyper transient.’ Through the use of redefinition and reclassification, parasites in an architectural or urban planning context are then able to be manipulated as a tool for propagation within the existing built environment. Space within cities and megacities are becoming more of a commodity, so by utilising these new parasitic tools, it is possible to manipulate space to allow for an increase in urban growth, whilst still being flexible enough to fit into pre-existing planning legislation globally.